Exploiting volumetric effects in novel additively manufactured open solar receivers. (1st November 2018) - Luque, S.; Menéndez, G.; Roccabruna, M.; González-Aguilar, J.; Crema, L.; Romero, M.
Highlights: Novel hierarchically-layered fractal-like solar receivers have been developed. Manufacturing to a high standard allowed by Selective Laser Melting techniques. Aft-shifted radiation absorption and convection-enhancing features introduced. Receivers experimentally showed to create and partially exploit volumetric effects. Overall thermal conversion efficiency is analysed, design guidelines are discussed. Abstract: The development of additive manufacturing techniques is allowing for the design of highly customised components with enhanced functionality in many application sectors. This paper describes the full aerothermal assessment of four novel hierarchically-layered fractal-like volumetric absorbers, designed to be employed in high temperature concentrating solar power applications. Absorbers are built by the lateral repetition of elementary cells on a 2D plane, which are arranged into constituent layers and stacked up following fractal growth patterns. They have been manufactured in stainless steel by selective laser melting. By fine tuning both the geometry of elementary cells and their growth patterns, the absorber porosity distribution can be tailored on a per-layer basis. This leads to optimised aft-shifted radiation absorption profiles and allows for the introduction of intricate convective heat transfer augmentation features. Experimental temperature measurements are presented which demonstrate that these variable porosity absorbers are able to generate and exploit volumetric effects, an advancement with respect to both monolithic honeycombs and isotropic foams. Solar-to-thermal conversion efficiencies, however, are shown to be of the same order as in those other receiver geometries. It is argued that the main reasons for this lie in the use of stainless steel, a material of relatively high reflectivity, and the predominantly low convective heat transfer rates found in the laminar flows established in these components.